THE RELATIONSHIP BETWEEN POST PARTUM DEPRESSION AND INFANTS FEEDING IN PMB SHANTINADEWI, KUTA MAKMUR DISTRICT, NORTH ACEH, 2023 - Khalidah Khalidah; Shantina Dewi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The relationship between post partum depression and breastfeeding for babies at PMB Shantinadewi, Kuta Prosperous District, North Aceh Regency in 2022 is descriptive analytic1. Research on 35 respondents at PMB Shantina Dewi, Kuta Makmur District, North Aceh Regency, as many as 22 pregnant women (62.8%) were breastfeeding their babies. 2. Obtained the relationship between Post Partum Depression and Breastfeeding in Infants, in this study. Chi-Square test results (X 2) 11,735 with a CI of 95% and 0.05 where P (0.03) (0.05). 11. Research on 35 respondents at PMB Shantina Dewi, Kuta Makmur District, North Aceh Regency, as many as 22 pregnant women (62.8%) were breastfeeding their babies. 2. Obtained the relationship between Post Partum Depression and Breastfeeding in Infants, in this study. Chi-Square test results (X 2) 11,735 with a CI of 95% and 0.05 where P (0.03) (0.05).